2007
DOI: 10.1088/0957-0233/18/5/003
|View full text |Cite
|
Sign up to set email alerts
|

Surface strain measurement: a comparison of speckle shearing interferometry and optical fibre Bragg gratings with resistance foil strain gauges

Abstract: The performance of two complementary optical strain measurement techniques, speckle shearing interferometry (shearography) and fibre Bragg grating (FBG) sensors, is compared with that of resistance foil strain gauges (RFSGs) and with theoretical predictions. The test object used for the surface strain measurements was a hydrostatically loaded ABS pipe. A multi-component shearography instrument, capable of full surface strain measurement, was used to determine the displacement gradient components, from which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…A plate centrally loaded by a weight was compared to the finite element analysis, resulting in a displacement gradient discrepancy of up to 12%. Another paper by Groves et al [10] compares measurements of a hydrostatically loaded PVC pipe with shearography, fibre Bragg sensors and resistive foil strain gauges. The discrepancy of the measured strain, between the shearography and the resistive foil strain gauges was, respectively for axial and hoop strains, up to 10% and 6%.…”
Section: Errors In Shearographymentioning
confidence: 99%
“…A plate centrally loaded by a weight was compared to the finite element analysis, resulting in a displacement gradient discrepancy of up to 12%. Another paper by Groves et al [10] compares measurements of a hydrostatically loaded PVC pipe with shearography, fibre Bragg sensors and resistive foil strain gauges. The discrepancy of the measured strain, between the shearography and the resistive foil strain gauges was, respectively for axial and hoop strains, up to 10% and 6%.…”
Section: Errors In Shearographymentioning
confidence: 99%
“…The graph shows the measured strain using shearography, a resistance strain gauge and a fibre Bragg grating. The shaded region indicates the standard deviation of a theoretical calculation [9].…”
Section: Qualitative Non-destructive Testingmentioning
confidence: 99%
“…The pipe was hydrostatically loaded before the reference frames were captured and then depressurized before the signal frames were recorded. Strain measurements from a hydrostatically loaded cylindrical pipe have been quantitatively compared with measurements obtained using resistance strain gauges and fibre Bragg grating instrumentation [9]. Some of the results of this investigation are shown in figure 25.…”
Section: Applications Of Quantitative Strain Measurement In Shearographymentioning
confidence: 99%
“…Recently, it has been demonstrated that shearography can be used to provide quantitative surface strain data from nonplanar surfaces with measurements that are comparable with resistive foil strain gauges and optical fibre Bragg grating strain measurements [9]. One of the issues with these systems is that the laser beams need to be guided to the correct illumination positions.…”
Section: Introductionmentioning
confidence: 99%